Purple Urine Bag Syndrome; Infeksi Saluran Kemih Langka Terkait Penggunaan Kateter Uretra Menetap - Wilda - Mahdani (Universitas Syiah Kuala, 2021)
Purple Urine Bag Syndrome (PUBS) is a rare phenomenon that is commonly overlooked. PUBS occurs in patients who use indwelling urinary catheters. This condition is characterized by a change in the color of urine including the bag and catheter tube turning purple. The purple color comes from the pigment mixture from the end result of the tryptophan metabolic chain reaction with the help of bacteria that produce sulfatase or phosphatase enzymes in the urine. The occurrence of PUBS requires the interaction of various risk factors simultaneously. PUBS can cause concern for patients, families and medical personnel. Lack of understanding and awareness can lead to misdiagnosis and treatment. For this reason, clinicians and medical personnel must be able to identify PUBS and understand its prevention and treatment. PUBS usually has a good prognosis. Correction of the underlying disease and treatment of symptomatic UTIs can reduce the chances of developing this syndrome.